2018
DOI: 10.1007/s00024-018-1814-0
|View full text |Cite
|
Sign up to set email alerts
|

Multichannel Singular Spectrum Analysis in the Estimates of Common Environmental Effects Affecting GPS Observations

Abstract: We described a spatio-temporal analysis of environmental loading models: atmospheric, continental hydrology, and non-tidal ocean changes, based on multichannel singular spectrum analysis (MSSA). We extracted the common annual signal for 16 different sections related to climate zones: equatorial, arid, warm, snow, polar and continents. We used the loading models estimated for a set of 229 ITRF2014 (International Terrestrial Reference Frame) International GNSS Service (IGS) stations and discussed the amount of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 59 publications
(61 reference statements)
2
12
0
Order By: Relevance
“…A change in CME variances arises from the fact that the environmental loading models remove much of CME variance (Fig. 10), especially with a frequency band between 9 and 12 cpy (cycles per year) mainly affected, which was also noticed before by Gruszczynska et al (2018). The above described results are consistent with the assertion that GNSS residuals are highly affected by environmental mass loading influences, mostly in the vertical direction.…”
Section: Ppca Filtering Of Real Time Seriessupporting
confidence: 81%
“…A change in CME variances arises from the fact that the environmental loading models remove much of CME variance (Fig. 10), especially with a frequency band between 9 and 12 cpy (cycles per year) mainly affected, which was also noticed before by Gruszczynska et al (2018). The above described results are consistent with the assertion that GNSS residuals are highly affected by environmental mass loading influences, mostly in the vertical direction.…”
Section: Ppca Filtering Of Real Time Seriessupporting
confidence: 81%
“…This estimate agrees with the ~60% of AML contributions evident from the GPS vertical position measurements (for 19 global stations) estimated by van Dam et al (1994). Our results agree with the recent study of Gruszczynska et al (2019) for the overall reduction of 68% for 229 global stations when compared to the environmental mass loading models.…”
Section: Discussionsupporting
confidence: 93%
“…Some studies (e.g., Dong et al, 2006; Yuan et al, 2008) found these crustal deformations to contribute to the spatially correlated “errors” in the GPS data. Recent studies (Gruszczynska et al, 2019; Gruszczynski et al, 2019; Zhu, Zhou, & Liu, 2017) have further explored the relation of CME with the environmental sources. Zhu, Zhou, Deng, et al (2017) examined the effects of environmental loading and thermal expansion on the estimated CME for a large network of the Crustal Movement Observation Network of China.…”
Section: Introductionmentioning
confidence: 99%
“…All the methods above are aimed at the GPS time series at a single GPS site, and are not conducive to the overall analysis of regional GPS observations. Actually, the seasonal signals at regional GPS sites have similar features [ 29 , 30 ]. Gruszczynska et al [ 30 ] used multichannel singular spectrum analysis (MSSA) to model the common seasonal signals in GPS observations in different regions around the world and without influencing the high frequency part of the spectra.…”
Section: Introductionmentioning
confidence: 99%
“…Actually, the seasonal signals at regional GPS sites have similar features [ 29 , 30 ]. Gruszczynska et al [ 30 ] used multichannel singular spectrum analysis (MSSA) to model the common seasonal signals in GPS observations in different regions around the world and without influencing the high frequency part of the spectra. Some other data-driven mathematical methods have been proposed to be used in modeling the geophysical signals from regional geodetic time series, e.g., principle component analysis (PCA) and independent component analysis (ICA), which have been widely used in smoothing and modeling GPS time series [ 15 , 23 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%